Cardamonin induces apoptosis of colorectal cancer cells via targeted inhibition of the JAK/STAT3/epithelial-mesenchymal transition (EMT) signaling axis - Wu, Min; Chen, Chuan; Ren, Dan; Du, Zuo; Liu, Zhenzhong; Liu, Wenhu (Frontiers in Pharmacology, 2026)
BackgroundColorectal cancer (CRC) remains a leading cause of cancer-related morbidity and mortality worldwide. Cardamonin (CDN), a bioactive flavonoid derived from the seeds of Alpinia katsumadai Hayata, has demonstrated broad-spectrum anticancer potential. However, its specific mechanisms and therapeutic targets in CRC remain poorly elucidated.MethodsNetwork pharmacology and molecular docking were employed to identify signaling pathways and targets associated with the anti-CRC activity of CDN. Cell viability, proliferation, migration, and invasion were evaluated using CCK-8, EdU, wound healing, and Transwell assays, respectively. Apoptosis and cell cycle were analyzed by flow cytometry. Proteomic profiling was applied to explore the underlying mechanisms, and the findings were validated using Western blot and functional assays. The antitumor efficacy of CDN in vivo was assessed using a subcutaneous xenograft mouse model.ResultsJAK1, STAT3, AKT1, EGFR, IL1B, and ESR1 were identified as shared core targets. The JAK/STAT3 pathway and apoptosis were recognized as pivotal mechanisms mediating the anti-CRC effects of CDN. In vitro, CDN inhibited proliferation, migration, and invasion of CRC cells, while promoting apoptosis. Mechanistically, CDN treatment reduced the levels of p-JAK1, p-JAK2, and p-STAT3, indicating inhibition of the JAK/STAT3 pathway. CDN also inhibited the epithelial-mesenchymal transition (EMT) in CRC cells. Consistent with the vitro results, in vivo, CDN led to a reduction in the volume and weight of xenograft tumors. It also inhibited the JAK/STAT3 signaling pathway, promoted apoptosis, downregulated Ki-67 expression, and attenuated EMT progression.ConclusionsCDN inhibits CRC progression and induces apoptosis by targeting the JAK/STAT3/EMT signaling axis, suggesting that CDN is a promising therapeutic agent for CRC.